2020
DOI: 10.11604/pamj.supp.2020.35.2.22963
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 knowledge, attitudes and practices in a conflict affected area of the South West Region of Cameroon

Abstract: Introduction since December 2019, the world is experiencing, the COVID-19 pandemic caused by the Virus SARS-CoV-2. It is feared that the pandemic maybe more devastating in conflict affected areas in the world. This study assessed the knowledge, attitudes and practices with regard to the COVID-19 in Buea municipality, Cameroon. Methods this was a cross-sectional study carried out in communities selected from 5 health areas of the Buea Health District. A questionnaire was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
45
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(62 citation statements)
references
References 7 publications
(6 reference statements)
7
45
7
Order By: Relevance
“…This finding is similar to a study done among Debre Birhan University students [34], Kingdom of Saudi Arabia [45], Tanzanian residents [37,46], China [33], Medical college students in Uttarakhand, India [32]. Adolescents are very eager to know emerging new events including the new novel virus (COVID-19) than adults [47]. Hence, students in the late age group are more knowledgeable compared to adults.…”
Section: Discussionsupporting
confidence: 86%
“…This finding is similar to a study done among Debre Birhan University students [34], Kingdom of Saudi Arabia [45], Tanzanian residents [37,46], China [33], Medical college students in Uttarakhand, India [32]. Adolescents are very eager to know emerging new events including the new novel virus (COVID-19) than adults [47]. Hence, students in the late age group are more knowledgeable compared to adults.…”
Section: Discussionsupporting
confidence: 86%
“…Following initial studies in China, coupled with the findings of Gautret et al (2020) (Boulware et al, 2020;Das et al, 2020;Cortegiani et al, 2020;Gao et al, 2020;Gautret et al, 2020), its use was endorsed among a number of governments and medical societies (Bokpe, 2020;Channnel News Asia, 2020;East African, 2020;Rich, 2020;Sciama, 2020;Tilangi et al, 2020). However, the lack of a comparator arm in the initial studies has been heavily criticised coupled with concerns with sideeffects including cardiac side-effects with hydroxychloroquine (International Society of Antimicrobial Chemotherapy, 2020; Gautret et al, 2020;ISAC/ Elsevier, 2020;Borba et al, 2020;Ferner and Aronson, 2020;Littlejohn, 2020) as well as reports of fatal overdoses (Abena et al, 2020;Das et al, 2020;GuruGamer, 2020;Nga et al, 2020;Politi, 2020). Recent studies have failed to demonstrate any clinical benefit for both the prevention and treatment of COVID-19 (Boulware et al, 2020;Geleris et al, 2020;Recovery Trial, 2020a;Rosenberg et al, 2020).…”
Section: Prevention and Treatment Of Covid-19mentioning
confidence: 99%
“…Surveys in the UK and US have also shown that participants generally had good knowledge about the main means of transmission and the common symptoms of COVID-19 ( Geldsetzer, 2020 ). In Cameroon, the population is also aware of the disease and preventive measures ( Nicholas et al., 2020 ). Further research is ongoing regarding why some people fail to adhere to suggested preventative measures, and we will be monitoring this ( Chan et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Our study evinced that a low fraction (11.5 %) of respondents was unconvinced with the government's efforts in ghting against COVID-19. To talk about other African nations, pertinently, 71 % and 60.9 % of Nigerians and Sudanese respectively are buoyant about the win against COVID-19 through their respective governmental actions [22,23]. Augmented attitude scores bore a direct correspondence with the age and education level in our study.…”
Section: Assessment Of Risk Of Infectionmentioning
confidence: 53%
“…Public knowledge and attitudes towards the disease is germane to adoption of appropriate practices, which are expected to eventually contain the disease. To facilitate outbreak management of COVID-19, many countries including various African nations (Egypt, Kenya, Sudan, Nigeria, Cameroon, Ghana and Tanzania [19][20][21][22][23][24][25]) piloted KAP surveys for their citizens, health workers as well as policy makers. The Ministry of Science and Higher Data-collection for this cross-sectional survey among Ethiopian citizens commenced on May 13, 2020 and concluded on May 25, 2020.…”
Section: Introductionmentioning
confidence: 99%